Sexual Abuse, Abuse of Concience and of Power: A New Definition - Murillo, José Andrés (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2020)
The present work aims to show the evolution of the definition of sexual abuse. It goes from a restricted and individual view, focused on the strictly genital violation, executed with force, misunderstanding the phenomenon of sexual abuse in vulnerable situations, facilitating the cover-up, the institutional denial and the re-traumatization of the victims. The evolution goes towards a more comprehensive, structural and ethical vision, which allows society, persons and institutions to assume their real responsibility in recognition and justice to victims. This is the way the society and Organizations can change from a culture of abuse and cover-up to a culture of care and lucid trust.
Keywords: child sexual abuse definition; cover-up; Catholic Church; lucid trust; vulnerability